The Dynamics of Community Participation in Establishing a Sustainable School Culture: Exploring the Role of Environmental Values in Adiwiyata Schools - Santosa, Heru; Supadi (Universitas Pendidikan Ganesha, 2024)
The role and participation of the school community are pivotal elements in fostering an Adiwiyata School culture based on environmental awareness values. This study aims to describe the roles and participation of the school community in implementing environmental awareness values to establish a sustainable Adiwiyata School culture. The research employed a descriptive qualitative approach, involving teachers, staff, students, and parents as research subjects. Data were collected through semi-structured interviews and document analysis. The findings reveal that the school community successfully supports the implementation of environmental awareness values through various initiatives, such as eco-friendly habits, green infrastructure development, and the integration of environmental awareness values into the curriculum. Active parental participation, combined with proactive efforts from school principals and teachers, emerged as key factors in the program’s success, despite the presence of some challenges. Evaluations conducted by the Environmental Agency and Adiwiyata Task Force members demonstrated the program’s effectiveness in adhering to Adiwiyata standards. These findings reflect the school’s commitment to sustainable environmental education. In conclusion, the roles and participation of the entire school community in implementing environmental awareness values have successfully built a strong, effective, and sustainable Adiwiyata School culture.